Are Workers' Remittances a Hedge Against Macroeconomic Shocks? : The Case of Sri Lanka - Ruiz-Arranz, Marta (IMF Working Papers; Working Paper ;, 2007)
We estimate a vector error correction (VEC) model for Sri Lanka to determine the response of remittance receipts to macroeconomic shocks. This is the first attempt of its kind in the literature. We find that remittance receipts are procyclical and decline when the island's currency weakens, undermining their usefulness as shock absorber. On the other hand, remittances increase in response to oil price shocks, reflecting the fact that most overseas. Sri Lankan are employed in the Gulf states. The procyclicality of remittances calls into question the notion that remittances are largely motivated by altruism.